On Mannheim Curves in Riemann-Otsuki Space R - O3 - Kucukarslan, Zuhal; Yilmaz, Munevver Yildirim (Soc Paranaense Matematica, 2013)
In this paper, we studied the Mannheim partner curves and their new characterizations are also obtained in Riemann - Otsuki space R - O-3.
Keywords: Riemann-Otsuki spaces; Mannheim curve; Frenet formula